Stem cell culture conditions and stability: a joint workshop of the PluriMes Consortium and Pluripotent Stem Cell Platform. (2nd April 2019) - Stacey, Glyn N; Andrews, Peter W; Barbaric, Ivana; Boiers, Charlotta; Chandra, Amit; Cossu, Giulio; Csontos, Lynn; Frith, Thomas JR; Halliwell, Jason A; Hewitt, Zoe; McCall, Mark; Moore, Harry D; et al.
Human stem cells have the potential to transform medicine. However, hurdles remain to ensure that manufacturing processes produce safe and effective products. A thorough understanding of the biological processes occurring during manufacture is fundamental to assuring these qualities and thus, their acceptability to regulators and clinicians. Leaders in both human pluripotent and somatic stem cells, were brought together with experts in clinical translation, biomanufacturing and regulation, to discuss key issues in assuring appropriate manufacturing conditions for delivery of effective and safe products from these cell types. This report summarizes the key issues discussed and records consensus reached by delegates and emphasizes the need for accurate language and nomenclature in the scientific discourse around stem cells. Lay abstract: Novel therapies derived from different kinds of precursor cells and stem cells are increasingly moving to clinical trials to restore tissue function in patients who have suffered injury or disease. The manufacture of these new therapies is unusually complex, which means that the manufacturing processes require great attention to assure they are safe and effective. This paper describes a conversation among experts in the field who are exploring therapeutic applications of two different kinds of stem cells (pluripotent stem cells and tissue-derived stem/precursor cells). It considers critical issues in developing the manufacturing process for each of these quite different cells types.